A Highly Enantioselective Approach to Hydrocarbazole Derivatives Catalyzed by Diphenylmethylidene Bis(oxazoline)‐Ni(II) Complexes. Issue 27 (14th July 2021) - Luo, Jia‐yu; Chenzhang, Peng‐fei; Lan, Wenjie; Li, Jia‐qi; Qin, Zhaohai; Fu, Bin
Abstract: The first Ni(II)‐catalyzed asymmetric [4+2] cycloaddition of silyloxyvinylindoles with 2‐enoyl pyridines was successfully accomplished by using a diphenylmethylidene‐tethered bis(oxazoline). A series of optically active hydrocarbazole derivatives with three contiguous stereocenters were achieved in good yield with both high diastereo‐(>20 : 1) and enantioeselectivities (up to 97 % ee) under mild conditions. Moreover, various 2‐enoyl azaarenes were compatible with the reaction. A proposed mechanism was deducted. Abstract : An efficient and highly stereoselective [4+2] cycloaddition of silyloxy vinylindole with 2‐enoyl azaarenes has been developed by using a diphenylmethylidene‐tethered bis(oxazoline), which afforded hydrocarbazole‐containing compounds bearing three contiguous stereogenic center in good yields with both high diastereo‐(>20 : 1) and enantioeselectivities (up to 97 % ee) under mild condition.